2020
DOI: 10.25259/sni_106_2020
|View full text |Cite
|
Sign up to set email alerts
|

External syringomyelia in longstanding benign foramen magnum tumors

Abstract: Background: The effect of benign foramen magnum tumours on cranial and spinal dimensions and cerebrospinal fluid (CSF) spaces is unclear. In this study, we measured alterations in cerebrospinal fluid (CSF) spaces in the spinal canal and in the posterior cranial fossa distant from the site of benign foramen magnum tumors. Methods: Twenty-nine magnetic resonance imaging scans of patients with foramen magnum tumors (8 meningiomas and 21 C2 neurinomas) were identified for radiological morphometric analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Goel et al reported in a study of cases with longstanding benign tumor at the foramen magnum were found to have significantly higher mean spinal canal diameter at both the C6 and T2 spinal levels than in controls. 2 Additionally, there was a marginal reduction even in the extent of syringomyelia (which extends from the C2 to the mid T7 level, compared with the previous lower border of T8) in our case report. This is the most extensively reported secondary syringomyelia compared with our literature review.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Goel et al reported in a study of cases with longstanding benign tumor at the foramen magnum were found to have significantly higher mean spinal canal diameter at both the C6 and T2 spinal levels than in controls. 2 Additionally, there was a marginal reduction even in the extent of syringomyelia (which extends from the C2 to the mid T7 level, compared with the previous lower border of T8) in our case report. This is the most extensively reported secondary syringomyelia compared with our literature review.…”
Section: Discussionsupporting
confidence: 40%
“…Tonsillar herniation and syringomyelia secondary to posterior cranial fossa meningiomas are rare entity, described as “external syringomyelia.” 2 Although the pathophysiological mechanism of syrinx formation secondary to posterior cranial fossa lesion is not yet clear, it implied that the mass effect of the posterior cranial lesion leads to tonsillar herniation that amounts to syringomyelia, an entity recently described by authors as an acquired Chiari malformation (ACM). 3 4 Unlike primary CM, in which syringomyelia is present in 30 to 70% of cases, the presence of syringomyelia in ACM was found to be 82%.…”
Section: Discussionmentioning
confidence: 99%
“…Goel et al reported in a study of cases with longstanding benign tumour at the foramen magnum were found to have signi cantly higher mean spinal canal diameter at both the C6 and T2 spinal levels than in controls [9] . Additionally, there was a marginal reduction even in the extent of syringomyelia (which extends from the C2 to the mid T7 level, compared to the previous lower border of T8) in our case report.…”
Section: Managementmentioning
confidence: 89%
“…Pathogenesis Tonsillar herniation and syringomyelia secondary to posterior cranial fossa meningiomas are rare entity, described as 'external syringomyelia' [9] . Although the pathophysiological mechanism of syrinx formation secondary to posterior cranial fossa lesion is not yet clear, it implied that the mass effect of the posterior cranial lesion leads to tonsillar herniation which amounts to syringomyelia, an entity recently described by authors as an Acquired Chiari malformation (ACM) [3,10] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 4 , 15 ] We reported the presence of external syringomyelia in benign foramen magnum tumors such as meningiomas and neurinomas. [ 16 ] Essentially, it appeared that both external syringomyelia and syringomyelia have a protective role; they can be indicators of presence of atlantoaxial instability and suggest the need for atlantoaxial stabilization [Figures 1 - 3 ]. Apart from their location inside or outside the neural structures, both syringomyelia and external syringomyelia have similar significance and both indicate the presence of segmental or multisegmental spinal instability.…”
mentioning
confidence: 99%